An electrospun polymer composite with fullerene-multiwalled carbon nanotube exohedral complexes can act as memory device. (24th April 2020) - Molinari, Fabricio N.; Barragán, Edwin; Bilbao, Emanuel; Patrone, Luciano; Giménez, Gustavo; Medrano, Anahí V.; Tolley, Alfredo; Monsalve, Leandro N.
Abstract: Functional polymer nanocomposites with distinctive electrical properties made of nanocarbon structures and biodegradable polymers are promising materials for the development of flexible and eco-friendly smart systems. In this work, a novel electrospun conductive polymer nanocomposite made of polycaprolactone with an exohedral complex made of multiwalled carbon nanotubes and fullerene C60 was prepared and characterized. The preparation was straightforward and the complexes self-assembled within the nanocomposite fibers. The nanocomposite showed electrical switching behavior due to charge accumulation of fullerene C60 upon electrical stimulation. Write-once read-many memory devices were fabricated by electrospinning a nanocomposite with 0.8%wt. fullerene C60 onto interdigitated coplanar electrodes. The device retained the ON state for more than 60 days and could be thermally reset, reprogrammed and erased with subsequent electrical and thermal cycling. Moreover, the electrical resistance of the device could be modulated by applying different programming voltage amplitudes and programming times, which revealed its adaptive behavior and potential application to neuromorphic systems. Graphical abstract: Image 1 Highlights: MWCNT-C60 Exohedral complexes were prepared and included within a polymer matrix. The nanocomposite was prepared using a biodegradable and biocompatible polyester. The electrospun conductive nanocomposite showed electrical switching behavior. WORM-type memory devices were fabricated by electrospinning using 0.8%wt. of C60. Devices showed adaptive behavior and potential application in neuromorphic systems.